Isolated single-stage DABSR DC/AC converter with series-power decoupling to interface PV with the single-phase grid - Chavez D. (2021)
This article presents an isolated single-stage Dual-Active-Bridge Series-Resonant (DABSR) DC-AC converter with series-power decoupling (SPD) to interface PV with the single-phase grid. A third port is added in the proposed DABSR DC-AC converter, which is series-connected on the AC side to power decoupling. Therefore, the electrolytic capacitors, typically used on the DC side, are replaced by film capacitors. The single-phase time-variant power is decoupled by controlling the time-variant voltage on the third port, which depends on the power amplitude, the filter capacitor and the grid frequency. A novel modulation is proposed where the grid and the third port voltages are modulated by unipolar PWM while the PV voltage is modulated by duty ratio. The power flow is controlled by phase-shift modulation. High efficiency is obtained due to soft-switching operation into all active bridges. Besides, low THD in the grid current is obtained. MPPT is performed with high accuracy. Finally, the proposed converter is compared with a similar DABSR DC-AC converter without SPD (WoSPD). The novel modulation, converter design and the control strategy are presented and validated by simulation. © 2021 IEEE.